The Role of Brand Image, Place and Service Quality in Increasing Customer Satisfaction for Noodle Culinary in Jember - Ningfiat, Nafira Ainur; Atika, Nur; Setyowati, Agustina; Qomariah, Nurul; Thamrin, Muhammad (Budapest International Research and Critics University, 2024)
Today's food business competition is required to have strategies that are able to attract and retain consumers for the sustainability of the company. This research aims to see the influence of brand image, location and service quality on customer satisfaction at Mie